2008
DOI: 10.1242/jeb.021980
|View full text |Cite
|
Sign up to set email alerts
|

Better mate in the shade: enhancement of male mating behaviour in the cabbage butterfly, Pieris rapae crucivora, in a UV-rich environment

Abstract: SUMMARYUltraviolet (UV) vision is widespread in a variety of animals, playing important roles in behaviours such as foraging and reproduction. Despite accumulated information about UV vision and UV-dependent behaviours of animals, little is known about the effect of temporal changes and local variations in UV light on UV-dependent behaviour. Here we report the mating behaviour of male cabbage butterfly, Pieris rapae crucivora, in environments with varying content of UV light. We first confirmed that the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…In this regard, it is interesting to note that a number of studies in aquatic and terrestrial ecosystems suggest that some herbivores effectively take advantage of the host leaves to protect themselves from direct solar radiation (Wahl 2008;Ohtsuka & Osakabe 2009). In addition, UV sensitivity is known to be used by some arthropods for visual mate choice (Li et al 2008b;Obara et al 2008), with a specific UV-B response demonstrated for jumping spiders (Li et al 2008b). The relative enhancement of short-wave UV radiation in the shade may facilitate mate location within the canopy, as discussed by Obara et al (2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is interesting to note that a number of studies in aquatic and terrestrial ecosystems suggest that some herbivores effectively take advantage of the host leaves to protect themselves from direct solar radiation (Wahl 2008;Ohtsuka & Osakabe 2009). In addition, UV sensitivity is known to be used by some arthropods for visual mate choice (Li et al 2008b;Obara et al 2008), with a specific UV-B response demonstrated for jumping spiders (Li et al 2008b). The relative enhancement of short-wave UV radiation in the shade may facilitate mate location within the canopy, as discussed by Obara et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, UV sensitivity is known to be used by some arthropods for visual mate choice (Li et al 2008b;Obara et al 2008), with a specific UV-B response demonstrated for jumping spiders (Li et al 2008b). The relative enhancement of short-wave UV radiation in the shade may facilitate mate location within the canopy, as discussed by Obara et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this result is that these low‐nitrogen diet fed males achieve high mating success by being less choosy. In P. rapae , not only females but also males exhibit mate choice (Obara, Koshitaka & Arikawa ; Obara et al . ; Tigreros unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…While the idea that UV coloration -invisible to humans -may serve as a 'private channel' of communication has been challenged (Cronin and Bok, 2016; but see Cummings et al, 2003), there is ample evidence that UV signals are important in animal communication (Rutowski, 1977;Johnsen et al, 1998;Smith et al, 2002;Cummings et al, 2003;Robertson and Monteiro, 2005;Kemp, 2008;Obara et al, 2008;Detto and Blackwell, 2009;Painting et al, 2016). However, although many butterflies have UVvisible color patches, in the absence of behavioral evidence, it is unclear whether the UV reflectance functions as a signal or whether it is simply an epi-phenomenon of the scale structure overlaying pigment granules.…”
Section: Introductionmentioning
confidence: 99%